Anthropology in the meantime : experimental ethnography, theory, and method for the twenty-first century - Fischer, Michael M. J., 1946- (Experimental futures., 2018)
In Anthropology in the Meantime Michael M.J. Fischer draws on his real world, multi-causal, multi-scale, and multi-locale research to rebuild theory for the twenty-first century. Providing a history and inventory of experimental methods and frameworks in anthropology from the 1920s to the present, Fischer presents anthropology in the meantime as a methodological injunction to do ethnography that examines how the pieces of the world interact, fit together or clash, generate complex unforeseen consequences, reinforce cultural references, and cause social ruptures. Anthropology in the meantime requires patience, constant experimentation, collaboration, the sounding-out of affects and nonverbal communication, and the conducting of ethnographically situated research over longitudinal time. Perhaps above all, anthropology in the meantime is no longer anthropology of and about peoples; it is written with and for the people who are its subjects. Anthropology in the Meantime presents the possibility for creating new narratives and alternative futures.